PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN IPS SISWA KELAS V SDN KALIBANTENG KIDUL 01 KOTA SEMARANG (APPLICATION OF COOPERATIVE LEARNING MODEL TYPE MAKE A MATCH TO ENHANCE QUALITY OF LEARNING SOCIAL (Jurnal Kreatif : Jurnal Kependidikan Dasar, 2011)
Based preliminary observation on the SDN Kalibanteng Kidul 01 Semarang. The writer found a problem in social fifth grade of learning. The teachers did not use an innovative learning model and instructional media, so it made the passive students have no spirit to follow the learning process. By implementing cooperative learning model type Make A Match is expected to improve the students achievment on social learning. Classroom action research was conducted with four steps they are planning, execution, observation and reflection using implement cooperative learning model type Make A Match. The subject of this research was the teacher and 48 students on the fifth grade of SDN Kalibanteng Kidul 01 Semarang, consist of 27 male and 21 female. The variables of this study were the skill of teachers, students activity, and students achievement. In this study, the writer using observation, test and documentation. And for the data analysis of this study using descriptive analysis. The result of this study showed an average score of teacherâ€™s skill in the cycle I was 3,5 with excellent category, the cycle II was 3,7 with excellent category and the cycle III was 3,9 with excellent category too. The average of student activity in cycle I was 3,0 with very good category, cycle II was 3,7 with very good category and the last in cycle III was 3,8 with very good category too. The exhaustiveness student learning in the initial condition only 2 from 48 students who achieve KKM (65). The average of process social learning which obtained by applying cooperative learning model of type Make A Match cycle I was 62,27 and 26 from 48 students experiencing learning exhaustiveness with percentage 54,16%. In cycle II was 71,46 and 36 from 48 students had studied with the percentage of completeness 75%. In cycle III was 79,90 and 41 from 48 students had studied with the thoroughness percentage 85,41%. Based on the resut of this study, it can be conclude that by applying a type of cooperative learning model Make A Match can improve the quality of learning social studies of the fifth grade of SDN Kalibanteng Kidul 01 Semarang. The advice that can be given is a model of cooperative type Make A Match is need to be applied and develope because it can improve teacherâ€™s skill, students activity and learning achievement so it can influence the improvement of social learning. Key Words: Cooperative Learning Model Type â€œMake A Matchâ€, the quality of learning social studies.